PENEGAKAN HUKUM TERHADAP PRAKTIK PERDAGANGAN KUCING KUWUK SEBAGAI SATWA LIAR DILINDUNGI - Sudrajat, Muhamad Rizki; Lukmanul Hakim, Aal; Djuniarsono , R. (Fakultas Hukum Universitas Islam Syekh Yusuf, 2024)
The leopard cat or Prionailurus Bengalensis is one of Indonesia's animal diversity and is a very valuable asset, and protection of this biodiversity is a must. One of the main threats is illegal trade and poaching for their exotic fur or as pets which also threatens the population of leopard cats. Based on the findings in this research, it can be concluded that even though the trade in protected animals has laws and regulations, there are still cases that continue to trade in protected animals, including leopard cats. Keywords: Leopard Cat, Protected wildlife, Law Enforcement